The captive duke - Burrowes, Grace (Burrowes, Grace. Captive hearts., 2023)
"Captured and tortured by the French, Christian Severn, Duke of Mercia, lost his wife, his son, and his will to live. He struggles to find a way back to the world he once knew until Gillian, Countess of Windmere, pointedly reminds him that he has a daughter who still needs him. As Christian and Gillian spend more and more time together trying to help Margaret, who was traumatized by her mother's death, their attraction slowly begins to grow"--